Non-attendance at urgent referral appointments for suspected cancer: a qualitative study to gain understanding from patients and GPs - Jefferson, Laura (Br J Gen Pract, 2019)
BACKGROUND: The 2-week-wait urgent referral policy in the UK has sought to improve cancer outcomes by accelerating diagnosis and treatment. However, around 5–7% of symptomatic referred patients cancel or do not attend their hospital appointment. While subsequent cancer diagnosis was less likely in non-attenders, those with a diagnosis had worse early mortality outcomes. AIM: To examine how interpersonal, communication, social, and organisational factors influence a patient’s non-attendance. DESIGN AND SETTING: Qualitative study in GP practices in one Northern English city. METHOD: In-depth, individual interviews were undertaken face-to-face or by telephone between December 2016 and May 2018, followed by thematic framework analysis. RESULTS: In this study 21 GPs, and 24 patients who did not attend or had cancelled their appointment were interviewed, deriving a range of potential explanations for non-attendance, including: system flaws; GP difficulties with booking appointments; patient difficulties with navigating the appointment system, particularly older patients and those from more deprived areas; patients leading ‘difficult lives’; and patients’ expectations of the referral, informed by their beliefs, circumstances, priorities, and the perceived prognosis. GPs recognised the importance of communication with the patient, particularly the need to tailor communication to perceived patient understanding and anxiety. GPs and practices varied in their responses to patient non-attendance, influenced by time pressures and perceptions of patient responsibility. CONCLUSION: Failure to be seen within 2 weeks of urgent referral resulted from a number of patient and provider factors. The urgent referral process in general practice and cancer services should accommodate patient perceptions and responses, facilitate referral and attendance, and enable responses to patient non-attendance.